(untitled) (Fiep Bulletin - online, 2019)
The cult of the body, a characteristic present in our society, is intensified in social networks. It demands, therefore, aseries of questions, some of them considered in the present article, with a view to their reception and propagation in the digitalculture or cyberculture. Under these conditions, we are primarily concerned with the consequences of such modeling of thoughtand sensitivity to corporeality. We affirm, in this text, that the cult of the body, considered in virtual means, is capable of provokingreal effects beyond what we perceive trivially. Thus, we need to problematize and demystify it, as we propose to accomplish in thisarticle.